Religion Market Abuses and Religious Conversion in Cameroon Urban Areas - Mpabe Bodjongo, Mathieu Juliot (Review of religious research, 2023)
This research note aims to examine the effect of religion market abuses on religious conversion, particularly on the non-transmission of religious preferences from parents to their offspring. Based on a field survey of 1,475 individuals in the cities of Douala and Yaoundé, this research note seeks to understand the dynamics of the socio-economic forces that lead to the abandonment of parents' religions. The econometric results reveal that the explanatory factors for changes in religious preferences often vary from one religion to another. With the exception of Pentecostals, Catholic, Protestant, and Muslim believers who believe that the religious market is rife with abuse are less likely to change their religious preferences. Increased income can significantly induce a change in religious preferences among Protestants and Pentecostals.